A comparison of particulate emission for rapeseed oil methyl ester, palm oil methyl ester and soybean oil methyl ester in perspective of their fatty ester composition. (5th February 2016) - Zhu, Lei; Cheung, C.S.; Huang, Zhen
Highlights: Particulate emissions of biodiesel with different compositions were compared. There is no obvious relationship between total unsaturates and smoke opacity. Smoke opacity is linear with polyunsaturate fraction of fuel at all test modes. SOF and total nucleation number concentration are linear with saturate fraction. Abstract: Three different kinds of biodiesel blended with baseline diesel fuel in 50% v/v were tested in a Cummins 4BTA direct injection diesel engine, with a turbocharger and an intercooler. Experiments were conducted under five engine loads of two steady speeds. The aim of this study is to identify the effects of fatty ester composition in the particulate emission of biodiesel from different feedstocks. The smoke opacity of SME50 (Soybean oil methyl ester) is higher than that of RME50 (Rapeseed oil methyl ester) and PME50 (Palm oil methyl ester). There is no obvious relationship between total unsaturate fraction and smoke opacity, while smoke opacity is linear with polyunsaturate fraction of fuel at all test modes, which means that the unsaturated ester with two or three double bonds have greater influence in smoke formation than the counterpart with only one double bond. The SOF (soluble organic fraction) proportion of RME50, PME50 and SME50 is 5 times or 4 times larger than that of diesel fuel and ultra-low-sulfur diesel respectively. The overall sequence of SOF is PME50 > SME50 > RME50. SOF fraction is linear with saturate fraction of fuel at all test modes. PME50 has higher nucleation particle number concentration than that of RME50 and SME50. Same with SOF, the increase in total nucleation number concentration depends on saturate fraction of fuel at all test modes. Thus, the feedstocks and composition of biodiesel could be selected and optimized during production process in order to improve the emission conditions of biodiesel.